Hubungan Antara Tingkat Stres dengan Psychological Well Being pada Lansia di Rumah Pelayanan Sosial Lanjut Usia Pucang Gading Semarang dan Wening Wardhoyo Ungaran - Cadela Gaby Metalia Putri Widodo; Iskim Luthfa; Muhammad Aspihan (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Background: As you get older, health problems increase, one of which is stress. Stress is very important because stress will have an impact on the quality of life and psychological well-being of the elderly. Psychological well-being in the elderly is the elderly's ability to accept themselves as they are, be able to build positive relationships with other people, be able to independently face social pressure, master the environment, have a purpose in life, and be able to realize one's potential in a sustainable manner. Stress in the elderly can describe that a person experiences a decrease in psychological well-being in the elderly which can be said to be low. Objective: This research is to analyze the relationship between stress levels and psychological well-being in elderly people at the Pucang Gading Semarang and Wening Wardoyo Ungaran Elderly Social Service Homes. Method: This research is a type of correlational quantitative research using the cross-section method. The sample taken in this study was 105 elderly people who were in the Pucang Gading Semarang and Wening Wardoyo Ungaran elderly service homes. The instrument for measuring stress levels and psychological wellbeing in the elderly uses a questionnaire. The test used in this research is the Gamma test. Conclusion: There is a relationship between stress levels and psychological wellbeing in the elderly at the Pucang Gading Semarang and Wening Wardhoyo Ungaran Social Service Homes for the Elderly.